PENGARUH PEMANFAATAN APLIKASI QUIZIZZ TERHADAP MOTIVASI BELAJAR MAHASISWA PGSD - Roswita Lioba Nahak; Viktorius Paskalis Feka (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2022)
Abstract. This study aims to describe the effect of using the Quizizz application on the learning motivation of students of the Elementary School Education Study Program (PGSD) at Citra Bangsa University, Kupang. This type of research uses quantitative research with quasi-experimental research methods. The population in the study were all PGSD second semester students who were guided by the researcher and took the Learning and Learning Theory course, totaling 53 students, while the sampling technique used saturated sampling, so that the number of samples was 53 students consisting of class A as the control class totaling 38 students and class B as the control class as many as 33 students. Collecting data using observation and questionnaire techniques, with research instruments used in the form of observation sheets and questionnaire sheets. Data analysis in this study used an independent t-test, but before analyzing the data the researchers also tested the data analysis requirements consisting of a normality and homogeneity test of data assisted by the SPSS version 16.00 application and showed the results that the learning motivation data for the control class and the experimental class were distributed normal, namely the value of sig. in the experimental class 0.200 > 0.05 and the control class 0.176 > 0.05 and the results of the data homogeneity test showed a significant value of 0.089 > 0.05, then both classes had the same variance (homogeneous). The results of the test of the difference in the average learning motivation of the control class and the experimental class also found that the average learning motivation of the experimental class was higher than the average learning motivation of the control class, namely 80.22>70.15 and the value of sig. the independent t-test also showed the results of 0.004 <0.005. Thus, it can be concluded that there is a significant effect of using the Quizizz application on students' learning motivation Keywords: Quizizz Application ; Motivation to learn Abstrak. Penelitian ini bertujuan untuk mendeskripsikan pengaruh pemanfaatan aplikasi quizizz terhadap motivasi belajar mahasiswa Program Studi Pendidikan Sekolah Dasar (PGSD) di Universitas Citra Bangsa Kupang. Jenis penelitian menggunakan penelitian kuantitatif dengan metode penelitian kuasi eksperimen. Populasi dalam penelitian adalah seluruh mahasiswa PGSD semester II yang diampu oleh peneliti dan mengikuti mata kuliah Teori belajar dan Pembelajaran yang berjumlah 53 mahasiswa, sedangkan teknik penarikan sampel menggunakan sampling jenuh, sehingga jumlah sampel sebesar 53 mahasiswa yang terdiri dari kelas A sebagai kelas kontrol berjumlah 38 mahasiswa dan kelas B sebagai kelas kontrol sebanyak 33 mahasiswa. Pengumpulan data mengunakan teknik observasi dan angket, dengan instrumen penelitian yang dipakai berupa lembar observasi dan lembar angket. Analisis data pada penelitian ini memakai uji independet t-test, tetapi sebelum dilakukan analisis data peneliti juga melakukan uji persyaratan analsis data yang terdiri dari uji mormalitas dan homogenitas data berbantuan aplikasi SPSS versi 16.00 serta menunjukkan hasil bahwa data motivasi belajar kelas kontrol dan kelas eksperimen berdistribusi normal yakni nilai sig. pada kelas eksperimen 0,200 > 0,05 dan kelas kontrol 0,176 > 0,05 dan hasil uji homogenitas data menunjukkan nilai signifikan 0,089 > 0,05, maka kedua kelas mempunyai varians yang sama (homogen). Hasil uji perbedaan rata-rata motivasi belajar kelas kontrol dan kelas eksperimen juga ditemukan bahwa rata-rata motivasi belajar kelas eksperimen lebih tinggi dibandingkan dengan rata-rata motivasi belajar kelas kontrol yakni 80,22>70,15 dan nilai sig. pada uji independent t-tes juga menunjukkan hasil 0,004<0,005. Dengan demikian dapat disimpulkan bahwa terdapat terdapat pengaruh pemanfaatan aplikasi quizizz yang signifikan terhadap motivasi belajar mahasiswa. Kata Kunci: Aplikasi Quizizz ; Motivasi Belajar